Resources recovery and reuse in sanitation and wastewater systems: Options and investment climate in selected South and Southeast Asian countries - Maksud Bekchanov; Pablo Evia (University of Bonn, Center for Development Research (ZEF), 2018)
Properly managed sanitation systems and improved wastewater treatment are important for safeguarding environment and enhancing sustainable livelihoods in vast areas of South and Southeast Asian countries. Recovering nutrients and energy from organic waste and wastewater is an effective option for improving environmental and health security, rehabilitating agricultural soils and improving energy and food access for the poor in these countries. This study addressed the technical potentials and investment climate for wider adoption of resources recovery and reuse (RRR) technologies in this region. Reviewing results and technical calculations indicated poor sanitation in India and Nepal in contrast to high levels of sanitation in Sri Lanka. However, despite comparatively higher levels of fecal sludge and wastewater treatment in Sri Lanka than the remaining countries, levels of waste treatment and recycling are much lower than their potential level in all countries of the region. Lack of financial resources, lack of awareness on hazardous impacts of poor sanitation, poor governance and high corruption levels in the system are pointed out as key barriers for wider implementation of waste and wastewater treatment and recycling technologies. Improving regulatory frameworks and governmental support through establishing subsidy programs, raising the awareness of population on environmental safeguarding, improving the skill capacity and technologies as well as ensuring quality standards can enhance wider implementation of RRR options.
Keywords: O13; Q53; O44; Q42; D02; 330; composting; biogas; nutrient management; organic waste; wastewater; onsite sanitation; soil rehabilitation; governance; institutional framework